Comparative safety and efficacy of tislelizumab-based regimens versus chemotherapy in lung cancer: a systematic review and meta-analysis - Ullah, Aman; Haider, Faseeh; Ahmed, Faizan; Arham, Muhammad; Dad, Allah; Tareen, Haseeb; Saleem, Fahad; Bakht, Kinza; Malik, Atif Nawaz; Afzaal, Zaima; Athar, Fatima Binte; Aman, Kainat; et al. (Frontiers in Oncology, 2025)
BackgroundLung cancer is the leading cause of cancer-related mortality worldwide, with its burden expected to rise significantly by 2025. Despite therapeutic advances, survival rates remain low, and comorbidities further complicate management. Economic projections indicate lung cancer will account for the highest share of cancer-related costs through 2050.ObjectivesTo evaluate the safety and efficacy of Tislelizumab with or without chemotherapy versus chemotherapy alone in lung cancer by synthesizing available evidence through meta-analysis.MethodologyThis meta-analysis followed PRISMA guidelines and was registered in PROSPERO. A systematic search of PubMed, Embase, Scopus, Cochrane Library, ScienceDirect, and ClinicalTrials.gov was conducted for RCTs comparing Tislelizumab-based regimens to chemotherapy in lung cancer (up to February 2025). Key outcomes included PFS, OS, ORR, DCR, and AEs. Bias was assessed using the Cochrane tool, and data were analyzed with random-effects models, incorporating subgroup and sensitivity analyses. Publication bias was assessed via funnel plots and Egger’s test.ResultsA total of six studies involving 2,148 patients were included in the meta-analysis. Tislelizumab-based regimens showed significant improvements in PFS (HR = 0.62, p < 0.0001) and OS (HR = 0.69, p < 0.0001) compared to chemotherapy alone. The ORR (RR = 1.49, p= 0.0001) and DCR (RR = 1.49, p= 0.0010) were significantly higher in the Tislelizumab group. The Tislelizumab group significantly reduced all-cause mortality (RR = 0.89, p = 0.0003). No significant differences were found in AEs (RR = 1.00, p= 0.75), except for ALT and AST elevations (RR = 1.36; 95% CI, 1.13–1.64) and (RR = 1.77; 95% CI, 1.17–2.67), respectively.ConclusionsTislelizumab-based regimens offer significant benefits over chemotherapy in lung cancer, with improved PFS, OS, and ORR. It significantly reduced all-cause mortality; however, the observed increase in ALT and AST underscores the need for vigilant liver function monitoring.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD42025641055, Identifier CRD42025641055.